Primaquine: report from CDC expert meeting on malaria chemoprophylaxis I. - Hill, DR; Baird, J; Parise, M; Lewis, L; Ryan, E; Magill, A (2006)
Primaquine phosphate has been used for preventing relapse of Plasmodium vivax and P. ovale malaria since the early 1950s, based on its ability to kill latent (hypnozoite) and developing liver stages of these parasites. There are three uses for primaquine in malaria: radical cure of established infection with P. vivax or P. ovale malaria; presumptive anti-relapse therapy (PART; terminal prophylaxis) in persons with extensive exposure to these parasites; and primary prophylaxis against all malaria species. All persons for whom primaquine is being considered must have a glucose-6-phosphate dehydrogenase (G6PD) enzyme level checked before use, and persons who have a deficiency of G6PD must not take primaquine for prophylaxis or PART. The recommended adult dose for PART based on clinical trials and expert opinion is 30 mg base daily for 14 days, started on return from a malarious region and overlapping with a blood schizonticide. The adult dose for primary prophylaxis is 30 mg daily begun 1 day before travel and continued for 7 days after return. This review will examine the evidence for these recommendations.